Desiccation of hemp seeds by high temperature micronization - S. V. Zverev (Пищевые системы, 2021)
In several cases, it is necessary to use heat treatment of cereal products to reduce moisture, inactivate some enzymes, increase storability and processing efficiency. One of the methods for heat treatment is high-temperature micronization — heating in a flow of infrared radiation. The method is convenient in the conditions of small and medium-sized enterprises. The aim of the study was to obtain the factual material regarding heating and desiccation of hemp seeds when heating in the flow of infrared radiation and modeling of the heating and desiccation processes. The experimental dependences of a seed temperature and moisture on heating time at different regimes of infrared heat treatment were obtained. Mathematical models were proposed for changes in a seed temperature as a function of time and moisture content depending on a seed temperature and the initial moisture. The desiccation models were based on simplified solutions of the system of differentiated equations of heat and mass transfer obtained by academician V. A. Lykov and his students. Model coefficients were identified by the results of the experiments. Analysis of the obtained coefficients shows that it is possible to use one coefficient in the examined models without a significant loss of the prognostic accuracy. The proposed models describe the experimental data quite well upon constant conditions of infrared heating of hemp seeds (irradiance and temperature in the treatment zone). However, heating conditions significantly affect the time dependence of the relative moisture (W/W0) and temperature increment ΔT(t). At the same time, it follows from the processing results and available experimental data that the character of the dependence W(ΔT) is determined by the initial moisture and is stable (that is, weakly depends on heating conditions).